(untitled) (Research, Society and Development, 2023)
Objective: The objective of the work was to correlate the level of motricity with the quality of life of children in the pandemic. Methodology: A cross-sectional, quantitative, descriptive and exploratory study was carried out, comprising a final sample of 75 schoolchildren, aged between 9 and 10 years, enrolled in public schools. The children answered a questionnaire about their sociodemographic and school profile in the pandemic. The assessment of motor performance took place through the EDM of Rosa Neto (2002), while the subjective perception of quality of life of the students through the AUQEI questionnaire. Results: The vast majority of students had a satisfactory level of quality of life (76%). When analyzing the domains separately, it was found that the item “autonomy” of those evaluated has a prevalence (92%) of students who showed dissatisfaction. It was noticed that the vast majority proved to be within the normal range for motor development levels (62.7%) and when associated with quality of life, no significant difference was confirmed (p<0.001) between the variables. However, it was observed that 33.3% of those evaluated who had a motor development classified as inferior, presented an unsatisfactory level regarding the subjective analysis of their quality of life and although 25% of the children who remained in the remote teaching and 37, 5% who remained in hybrid teaching had a deficit in motor age. Conclusion: It was concluded that there was no significant association between the variables of motor development and quality of life. However, the domain “autonomy” is visibly affected.